2011
DOI: 10.5336/medsci.2010-17952
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Stability, Cyclin D1 and Frizzled Proteins Expression in Human Breast Cancer and Their Relation with the Prognosis

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Aberrant Wnt signaling pathway activation and stabilization of β-catenin protein is associated with tumorigenesis and human breast tumors. We have examined β-catenin, cyclin D1, sFRP1 and sFRP2 expressions in the breast cancer and effects of these factors on prognostic parameters in patients with breast cancer. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : One hundred and seventeen consecutive female malignant breast tumor patients were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…On the other hand, contradictory to our results, He et al reported significant correlation of β-catenin and cyclin D1 over expression with the differentiation grade, clinical stage and lymph node status of breast cancer patients [19]. Apart from this, Zengel, et al failed to find any correlation of clinic pathological parameters with β-catenin or cyclin D1 in breast cancer patients [20].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, contradictory to our results, He et al reported significant correlation of β-catenin and cyclin D1 over expression with the differentiation grade, clinical stage and lymph node status of breast cancer patients [19]. Apart from this, Zengel, et al failed to find any correlation of clinic pathological parameters with β-catenin or cyclin D1 in breast cancer patients [20].…”
Section: Discussioncontrasting
confidence: 99%
“…Cyclin D1 expression was not of prognostic value in early stage breast cancer patients [30]. Contradictorily, higher expression of cyclin D1 was associated with better prognosis in breast cancer patients with Her2 over expression [20,31]. In conclusion, the over-expression of the Wnt pathway components is likely to have a role in early stages of breast cancer development leading to the cancer progression.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations